2021
DOI: 10.3390/land10040372
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Biochar-Swine Manure Mixture to Conventional Manure Impact on Soil Nutrient Availability and Plant Uptake—A Greenhouse Study

Abstract: The use of swine manure as a source of plant nutrients is one alternative to synthetic fertilizers. However, conventional manure application with >90% water and a low C:N ratio results in soil C loss to the atmosphere. Our hypothesis was to use biochar as a manure nutrient stabilizer that would slowly release nutrients to plants upon biochar-swine manure mixture application to soil. The objectives were to evaluate the impact of biochar-treated swine manure on soil total C, N, and plant-available macro- and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Results comparing the changes in manure properties confirmed that acidic biochar could mitigate NH3 emissions and likely prevent nitrogen loss in the manure. Manure treated with biochar powder showed benefits to soil health, lowered nutrient runoff risk, and the potential for agronomic benefits to corn and soybeans (Banik et al, 2021a(Banik et al, , 2021b shown on lab and greenhouse scales. In addition, more techno-economic analyses are warranted on the potential savings due to the nutrient retention in manure, as the average cost of anhydrous ammonia is $526/ton (USDA, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results comparing the changes in manure properties confirmed that acidic biochar could mitigate NH3 emissions and likely prevent nitrogen loss in the manure. Manure treated with biochar powder showed benefits to soil health, lowered nutrient runoff risk, and the potential for agronomic benefits to corn and soybeans (Banik et al, 2021a(Banik et al, , 2021b shown on lab and greenhouse scales. In addition, more techno-economic analyses are warranted on the potential savings due to the nutrient retention in manure, as the average cost of anhydrous ammonia is $526/ton (USDA, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Biobased-fuels production, waste-to-carbon, and waste-to-energy thermal processes result in a relatively low-value biocoal. Circular economy opportunities exist for the valorization of biochar and the improvement of sustainability in animal and crop production systems (Banik et al, 2021a;Banik et al, 2021b). The long-term goal is to test and scale up the treatments from laboratory-scale to farm-scale, keeping in mind the techno-economic constraints for many swine farmers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biobased-fuel production, waste-to-carbon, and wasteto-energy thermal processes result in a relatively low-value biocoal. Circular economy opportunities exist for the valorization of biochar and the improvement of sustainability in animal and crop production systems [22,23]. The long-term goal is to test and scale up the treatments from the laboratory scale to the farm scale, keeping in mind the techno-economic constraints for many swine farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, synergistic effects to biochar use could be achieved for the animal-crop production system. First, biochar can be used to mitigate gaseous emissions from manure, and then the biochar and manure mixture can be used as a better-quality fertilizer, improve the soil nutrients content, and minimize the nutrient losses from soil [22,23]. Therefore, innovative biochar treatment could be a one-stop solution to solve the gaseous emissions and improve agriculture's sustainability.…”
Section: Introductionmentioning
confidence: 99%